Diseño del proceso de obtención de una resina alquídica elaborada a base de aceites vegetales a nivel laboratorio en Sigra S.A. (2019)
The project presented below consists of the design of the process of obtaining an alkyd resin based on vegetable oils on a laboratory scale at the company Sigra S.A. This project is carried out based on a bibliographic review of the methods of obtaining alkyd resin, the above is done in order to identify the variables with more influence on the process and at the same time propose a design of experiments that allow obtaining a good quality alkyd resin according to regulations. Bibliographic research focuses mainly on the different reactive routes through which the obtaining of an alkyd resin can be carried out, thus listing variables such as residence time, temperature, agitation, raw materials, vegetable oils and percentage of oil in the resin. To formulate an experimental methodology that makes it possible to obtain the desired final product, an experimental check of the bibliography is developed identifying whether the variables listed have a significant influence or not on the final product, thus generating information that allows structuring the appropriate methodology and develop the experiment design with the most prominent variables in the experimental verification. The main objective of the experiment design is to perform an analysis of the final product based on the quality parameters (ASTM D1725 and ASTM D1639) and thus establish the specific conditions to propose an industrial escalation and after that, estimate the costs of the final product.